Learning Motivation among Students Participating in a Private Arabic Language Program at Al-Fatih Private Tutoring Institution - Nida Ul Khasanah; Ganjar Yusup Sofian; Agung Heru Setiadi; Adamu Abubakar Muhammad; Khoirotul Imro'ah Qohar (Diwan Media Pustaka, 2026)
This study examines the importance of learning motivation in supporting students’ success in an Arabic private tutoring program. Arabic learning often presents challenges, particularly in vocabulary, Arabic syntax, morphology, and Arabic text reading. This study aims to describe students’ learning motivation in joining the Arabic Private Tutoring Program at Al-Fatih Private Tutoring Institute. It also identifies the supporting and inhibiting factors that influence their motivation. This study employed a descriptive qualitative approach. The researchers collected data through interviews, observation, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that students’ initial motivation was generally influenced by parental encouragement, academic needs, and the desire to understand religious lessons. However, after participating in the private tutoring program, students’ motivation developed into intrinsic motivation. They felt more comfortable, confident, and supported in understanding Arabic. The main supporting factors included patient tutors, gradual learning methods, a conducive learning environment, and parental support. The inhibiting factors included difficulties in understanding Arabic grammar and limited independent practice. This study concludes that the Arabic private tutoring program plays an important role in fostering students’ learning motivation. It also improves their self-confidence and strengthens their basic Arabic language competence.